EVALUATION ON ONLINE PLATFORMS IN ENGLISH LANGUAGE TEACHING AT SMP FITRA ABDI PALEMBANG - Vivi Alvionita; Aswadi Jaya; Hermansyah (Esteem Journal of English Education Study Programme, 2024)
This study aims to evaluate on online platforms in English language teaching at SMP Fitra Abdi Palembang. The research focused on eighth – grade students at SMP Fitra Abdi Palembang of the 2023/2024 academic year, with the total of 31 students. The researchers using a descriptive qualitative research method that typically involves detailed data to provide a comprehensive understood of a phenomenon. And utilized the data collection techniques with a questionnaire, and interviews. Additionally, the results of the questionnaires showed 3305 of a total score of, indicated that students used online platforms in learned English. In conclusion showed that most eighth – grade students at SMP Fitra Abdi Palembang used the Duolingo app to learned English instead of used Hello Talk app and Beelinguapp.